Portopulmonary Hypertension - Savale, Laurent; Watherald, Jason; Sitbon, Olivier (Seminars in Respiratory and Critical Care Medicine, 2017)
Portal hypertension may have major consequences on the pulmonary vasculature due to complex pathophysiological interactions between liver and lungs. Portopulmonary hypertension (PoPH) is characterized by the association of portal hypertension and pulmonary arterial hypertension (PAH). As progressive elevation of right ventricular afterload can lead to right heart failure, PoPH is a serious complication of portal hypertension, affecting functional status and prognosis of patients. Early detection by transthoracic echocardiography must be performed in symptomatic patients and in candidates for liver transplantation (LT). Right heart catheterization remains mandatory to confirm the diagnosis and exclude all other causes of elevated pulmonary pressures. The management of PoPH includes PAH-targeted therapies although few studies have evaluated these medications in this specific indication. The impact of LT on PoPH outcome remains complex and must be specified by future collaborative investigation. Although uncontrolled PoPH is associated with higher risk of postoperative right heart failure and death, stabilization, improvement, or normalization of pulmonary hemodynamics after LT seem to be achievable goals in selected patients with PoPH.
Keywords: hypertension; pulmonary; pulmonary arterial hypertension; portal hypertension; cirrhosis; liver transplantation; survival